2021
DOI: 10.1177/10883576211023349
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence Base for Interventions for Individuals With ASD: A Call to Improve Practice Conceptualization and Synthesis

Abstract: Identifying potentially effective practices for improving outcomes for individuals with autism spectrum disorder (ASD) is a complex process. In this article, we respond to recent reviews of evidence-based practices for individuals with ASD. We identify possible problems and make suggestions in relation to identifying well-specified practices, inclusion of gray literature, and considering use of studies with noneffects in systematic reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Although imperfect (cf. Ledford et al, 2021), the processes by which evidence from single‐case designs are accumulated and understood are fairly well accepted and large‐scale summative efforts have already made a substantial impact on the visibility of those techniques most likely to influence client performance (e.g., Horner et al, 2005; Steinbrenner et al, 2020). However, the ways in which effective practitioners come to select, draft, adjust, and match techniques to circumstance in the service of valued outcomes is not well understood (Bruhn et al, 2020) and clinical judgment has been a white whale which continues to elude operationalization efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Although imperfect (cf. Ledford et al, 2021), the processes by which evidence from single‐case designs are accumulated and understood are fairly well accepted and large‐scale summative efforts have already made a substantial impact on the visibility of those techniques most likely to influence client performance (e.g., Horner et al, 2005; Steinbrenner et al, 2020). However, the ways in which effective practitioners come to select, draft, adjust, and match techniques to circumstance in the service of valued outcomes is not well understood (Bruhn et al, 2020) and clinical judgment has been a white whale which continues to elude operationalization efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as with other interventions identified as evidence-based (cf. Ledford et al, 2021), there are also a multitude of instances in which these procedures do not lead to improvements in stereotypy.…”
Section: Treating Stereotypymentioning
confidence: 99%
“…They identified these procedures as being evidence based for improving a wide variety of outcomes: academic behaviors, adaptive behavior, challenging behaviors, communication, motor skills, play skills, school readiness (e.g., engagement), and social behaviors. However, the procedures and resulting findings from this large-scale review have been identified as potentially problematic (Leaf, 2021;Ledford et al, 2021). Importantly, because this review only included studies with positive outcomes, it does not provide information about negative or equivocal findings.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Addressing calls for more specific investigations into subtypes of EBPs, we took a novel approach to autism EBP exploration by attending to both multicomponent practices and strategies ( 51 ). To develop a set of multicomponent practices and strategies that are used to support meaningful inclusion and retention of autistic children in general education settings, we used explicit criteria for exclusion of practices from the NPDC review—practices could not: (1) be assessments (e.g., functional behavior assessment); (2) implemented only outside of schools (e.g., parent-implemented); or (3) require certification (e.g., Pivotal Response Training, Sensory Integration Therapy).…”
Section: Methodsmentioning
confidence: 99%